2017
DOI: 10.1177/1010428317692258
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of hypermethylation and reactivation of glutathioneS-transferase pi 1 gene by curcumin in breast cancer cell line

Abstract: One of the mechanisms for epigenetic silencing of tumor suppressor genes is hypermethylation of cytosine residue at CpG islands at their promoter region that contributes to malignant progression of tumor. Therefore, activation of tumor suppressor genes that have been silenced by promoter methylation is considered to be very attractive molecular target for cancer therapy. Epigenetic silencing of glutathione S-transferase pi 1, a tumor suppressor gene, is involved in various types of cancers including breast can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 18 publications
1
26
0
1
Order By: Relevance
“…HCC-38 is a triple-negative breast cancer (TNBC) cell line, UACC-3199 is estrogen receptor-negative/progesterone receptor-negative (ER -/PR -), and T47D is ER + /PR + . Based on previous studies (29,30,38,39), we treated the cells with 5 and 10 µM of curcumin. To investigate the effect of these curcumin concentrations on cell proliferation, we monitored cell proliferation in the presence of curcumin over a total period of 6 days.…”
Section: Curcumin Suppresses the Proliferation Of Hcc-38 Uacc-3199 mentioning
confidence: 99%
See 1 more Smart Citation
“…HCC-38 is a triple-negative breast cancer (TNBC) cell line, UACC-3199 is estrogen receptor-negative/progesterone receptor-negative (ER -/PR -), and T47D is ER + /PR + . Based on previous studies (29,30,38,39), we treated the cells with 5 and 10 µM of curcumin. To investigate the effect of these curcumin concentrations on cell proliferation, we monitored cell proliferation in the presence of curcumin over a total period of 6 days.…”
Section: Curcumin Suppresses the Proliferation Of Hcc-38 Uacc-3199 mentioning
confidence: 99%
“…Several studies have shown that this herb can exert anticancer effects, on breast cancer in particular, by targeting various signaling pathways (27). Furthermore, it has been reported that curcumin can function as a DNA methylation inhibitor in breast cancer cells (28)(29)(30)(31)(32). Nevertheless, curcumin's potential as a DNA methylation inducer remains to be fully explored.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier gene candidate studies performed in murine RAW 264.7 macrophage cells and TRAMP C1 prostate cancer cells delivered evidence for curcumin‐mediated demethylation and activation of Nrf2 , a potent activator of antioxidant pathways (Khor et al, ). Another member of the antioxidant network, GSTP1 , was also found to be demethylated and activated upon exposure of breast cancer cells to curcumin (Kumar, Sharma, & Rathi, ). Furthermore, Maugeri et al () reported up‐regulation of DNMT1 expression and activity along with oxidative stress induced by chronic high glucose levels in a cellular model of diabetic retinopathy (Maugeri et al, ).…”
Section: Interrelationship Between Antioxidant Properties and Dna Metmentioning
confidence: 99%
“…Earlier gene candidate studies performed in murine RAW 264.7 macrophage cells and TRAMP C1 prostate cancer cells delivered evidence for curcumin-mediated demethylation and activation of Nrf2, a potent activator of antioxidant pathways (Khor et al, 2011). Another member of the antioxidant network, GSTP1, was also found to be demethylated and activated upon exposure of breast cancer cells to curcumin (Kumar, Sharma, & Rathi, 2017 CDKN2A at a non-invasive breast cancer stage , PTEN and RARβ2 in breast cancer cells (Lubecka-Pietruszewska et al, 2015), and RARβ, CDH1, DAPK1, and GSTP1…”
Section: A Link Between Antioxidant Properties Of Curcumin and Curcmentioning
confidence: 99%
“…В умовах in vitro у клітинах лінії раку молочної залози MCF-7 куркумін інгібував метилювання промотора GSTP1 шляхом блокування каталітичного тіола-ту ДНК метилтрансферази 1 і це призводило до повторної експресії протеїну GSTP1 (Kumar et al, 2017).…”
unclassified